Social Media and Migration Decisions: An Analysis of popular Facebook Groups and Twitter Handles and their role in the decisions migration of highly mobile Nigerian Youth - Opia, Chinyere (Université d'Ottawa | University of Ottawa, 2021)
People move within countries and across borders, looking for better employment opportunities and improved socio-economic wellbeing. In contemporary societies, migration is being enabled by technological advances. The mixture of social media is shifting dimensions. Social media has shifted sources of information on migration from the real to the virtual world. In this paper I examine how migrants use social media during migration processes and how the information gathered influences their migration decisions. While literature has considered the role of social media in facilitating migration (Dekker and Engbersen 2014), the moves by governments to encourage or discourage migration using social media—has not been extensively studied particularly as it shapes migration decisions of Nigerian youth. My aim is to explain the role of social media contents by users—including government agencies—and how they shape migration decision making process of upwardly mobile Nigerian youth who use Facebook and Twitter. Data for this research was collected from Facebook groups and Twitter conversations on migration. These engagements were analyzed and presented by the key emerging themes and supported by literature and concepts to generate a better understanding of social media and migration decisions, processes, and outcomes. Understanding the role of social media and migration decisions of upwardly mobile Nigerian youth helps to understand international migration in a networked society.